Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages power-politics is being played at the Meetings of the Security Council and of the Foreign Ministers. The Labour Government cannot be absolved from the charge of participation in this catastrophic gamble ; if its sins of commission are confined to anachronistic vapourings about the Empire, timid subservience to U.S.A., the snubbing of friends and the employment of Tories in diplomatic posts, its sins of omission are more vividly displayed in ignoring the democratic and socialist movements in Western Europe and in ex-enemy countries, in doing little or nothing about the democratic rehabilitation of the Colonies and in the complete absence of any comprehensive, integrated and clearly formulated statement of Socialist Britain's desire for a Socialist world. A truly socialist foreign policy is not concerned with being pro-Soviet or pro-U.S.A. ; it is concerned with promoting democratic socialism everywhere and with furthering every international action which will increase understanding and goodwill among democratic peoples. This policy implies an unalterable hostility to every manifestation of fascist totalitarianism. Temporising with dictators means losing our friends ; we cannot afford to lose the few we have retained. If we want peace, we must also want the things which belong to our peace. Despite the orgy of mutual back-slapping at the Bournemouth Conference, it is manifest that much of the enthusiasm engendered by Labour's resounding victory has been undermined by an awareness that much of the glory has departed. There is a marked absence of inspiration. To ascribe this solely to post-war fatigue is dangerous complacency. The people are tired, very tired of the mess and waste of war ; they can still be inspired by proofs that the fruits of victory are within their reach. Common Wealth believes that Labour ought to have asked for, and could have obtained, an electoral mandate for a much wider and more fundamental policy of socialisation. Mr. Morrison tells us that, when the full programme of nationalisation has been carried out, 80 per cent. of the country's industrial wealth will still be in capitalist hands. This is what the Yorkshire Post (June 24th, 1946) thinks of Mr. Morrison as an economist: "No member of the Government can talk better sense than Mr. Morrison... We have seen speeches of his on the economic needs of the present situation which might stand as models of sound Conservative policy." (our italics). Well may the Tory Press praise him ; they know well enough that no modest reformist programme of piecemeal nationalisation, concentrated mainly on semi-bankrupt industries, accompanied by full compensation for the descendants of generations of economic parasites, can threaten the inner stronghold of capitalism. Moreover, because such nationalisation takes place within a capitalist framework and is concerned 2 15X/2/98/21